2018
DOI: 10.1042/bcj20180706
|View full text |Cite
|
Sign up to set email alerts
|

Rhodobacter sphaeroides methionine sulfoxide reductase P reduces R- and S-diastereomers of methionine sulfoxide from a broad-spectrum of protein substrates

Abstract: Methionine (Met) is prone to oxidation and can be converted to Met sulfoxide (MetO), which exists as R- and S-diastereomers. MetO can be reduced back to Met by the ubiquitous methionine sulfoxide reductase (Msr) enzymes. Canonical MsrA and MsrB were shown to be absolutely stereospecific for the reduction of S-diastereomer and R-diastereomer, respectively. Recently, a new enzymatic system, MsrQ/MsrP which is conserved in all gram-negative bacteria, was identified as a key actor for the reduction of oxidized per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…This seems to be the case at least for MsrP in Rhodobacter sphaeroides . Indeed, Tarrago and co-workers have shown that when the periplasmic extracts of this bacterium are treated with NaOCl and then incubated with MsrP, those MetO sites next to glutamate and/or aspartate were more efficiently reduced back to methionine [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be the case at least for MsrP in Rhodobacter sphaeroides . Indeed, Tarrago and co-workers have shown that when the periplasmic extracts of this bacterium are treated with NaOCl and then incubated with MsrP, those MetO sites next to glutamate and/or aspartate were more efficiently reduced back to methionine [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Canonical MsrA and MsrB have been shown to be absolutely stereospecific for the reduction of Met-S-O and Met-R-O, respectively [ 8 ]. More recently, a new enzymatic system, MsrQ/MsrP, which can reduce both R- and S-diasteroisomers has been described in gram-negative bacteria [ 9 ]. Thus, like phosphorylation, methionine oxidation is a reversible covalent modification that has been demonstrated to both up regulate [ 10 , 11 , 12 ] and down regulate [ 13 , 14 ] protein activity through the direct sulfoxidation of specific methionine residues.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the enzymes belonging to the DMSO reductase family have a more complex catalytic center constituted of two molybdopterin guanosine dinucleotides coordinating the Mo atom [18]. The periplasmic methionine sulfoxide reductase (MsrP) belongs to the sulfite oxidase family and was recently shown to be a non-stereospecific protein-MetO reductase with a broad range of protein substrates [19,20]. MsrP is present in most Gram-negative bacteria and genetic characterizations in Escherichia coli and Azospira suillum indicated that it is principally involved in protein oxidation protection during stress induced by reactive chlorine species [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…The MsrA, MsrB, and MsrP are the only enzymes for which the ability to reduced MetO in oxidized protein was experimentally demonstrated [9,10,19,20]. On the contrary, biochemical assays demonstrated that neither the fRMsr, BisC, nor TorZ/MtsZ can catalyze the reduction of MetO in proteins [15,16,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation